Avaliação de desempenho multicritério do capital intelectual em uma universidade pública brasileira - Baldo, Afonso Romano Brustolin (2022)
Driven by external demands, universities have sought ways to improve and reinforce their value, transparency, and competitiveness, seeking ways to assess and measure intellectual capital (IC). The literature has proposed several measurement models, with a main focus on the ranking and disclosure of the IC, however, these models leave the role of the decision-maker and the management of the IC in the background. Therefore, the research aims to build a constructivist multicriteria model for evaluating the IC performance of a Brazilian public university. Initially, a bibliographic research procedure was used, of descriptive nature, a qualitative approach in the identification of articles, and a quantitative approach in the analyses, using the Knowledge Development Process – Constructivist (ProKnow-C) as an intervention instrument to carry out a literature review. Subsequently, field research was carried out, of an exploratory nature, problem of a qualitative and quantitative approach, using the Multicriteria Decision Aid - Constructivist (MCDA-C) methodology as an intervention instrument, which resulted in the construction of a constructivist multicriteria performance evaluation model. The main results of the literature review were: the identification of a bibliographic portfolio of 18 articles, from which it was possible to identify that: the articles use generic IC measurement models; most measurements are based on data from annual reports or university strategic plans; absence of research with a constructivist bias, which considered the values and perceptions of the decision maker, as well as the singularity of the context in the construction of the models; and absence of articles that recommended actions to improve the performance of the IC, thus supporting the decision-making process. The construction of the constructivist multicriteria model, fulfills the objective of the research and fills the gaps found in the literature as an IC assessment instrument, which generates knowledge in the decision-maker, allows the diagnosis of the current situation and to generate improvement actions for the university's IC. In the construction of the model, 17 primary evaluation elements were identified, which generated 72 concepts, divided into four fundamental points of view (FPsV): “structural”, “organizational”, “excellence in teaching, research and extension”, and “regional development”. These FPsV unfolded in elementary points of view (EPsV) and in the construction of 49 descriptors with measurement scales. After verifying the status quo of each descriptor, the global assessment of the university's IC was verified, which is competitive, with 17.32 points. At the end of the model, actions were recommended to improve the performance of the criteria that had compromising performance. Comparing the literature with the model constructed, there was a similarity in the categories, subcategories, and indicators of the IC. However, the proposals and approaches found, differ in the sense that the indicators in the literature have a statistical nature, establishing what and how to measure, but they do not advance in the sense of allowing a diagnosis guided on evaluating the result based on a reference performance, nor process to generate improvement actions. Which is supplied by this work. In this way, the research fills the gaps in the literature and presents, based on the decision-maker vision and values, a constructivist multicriteria model for evaluating IC performance in a Brazilian public university.